Uji Aktivitas Antioksidan Fraksi N-Heksan Dari Akar Tanaman Qust Al Hindi (Saussurea lappa) Menggunakan Metode DPPH - Nurul Muthmainnah Salam; Sukmawati Syarif; A. Muflihunna (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Qust Al Hindi (Saussurea lappa) is a type of medicinal plant which is used as an antioxidant, anticancer, anti-inflammatory and antimicrobial because it contains phytochemical compounds such as flavonoids, terpenoids, and alkaloids.In addition, there are also chlorogenic acid compounds that function as antioxidants. This study aims to analyze the antioxidant activity of the n hexane fraction of the roots of Qust al Hindi (Saussurea lappa) using the DPPH free radical scavenging method. This type of research is a laboratory experiment using a spectrophotometer method based on calculating the IC50 value of the n-hexane fraction of the sample on DPPH free radical activity. The stages of this research began with sample preparation, sample extraction and fractionation, measurement of maximum wavelength, and testing of the antioxidant activity of the sample n-hexane fraction and quarcetin standard. The results of this study are for the percent reduction of 35,26%; the regression equation value of the sample n-hexane fraction is y = 0,0652x + 12,305 ( r = 0,9996 ); and IC50 value of 284,6 µg/mL. The results of study illustrate that the n-hexane fraction of the roots of qust al hindi has potential as an antioksidant activity against DPPH free radical.